Achieving short ignition delay and high specific impulse with cyanoborohydride-based hypergolic ionic liquids. (26th October 2022) - Pialat, Amélie; Kitos, Alexandros A.; Witkowski, Tomasz G.; Cook, Cyril; Wang, Shiliang; Hu, Anguang; Murugesu, Muralee
Abstract : A new family of HILs, based on substituted 1 H -1, 2, 4-triazol-4-ium, pyrrolidinium, ammonium and pyridinium cations and a cyanoborohydride anion, is introduced, with higher heats of formation, heats of combustion and specific impulse compared to dimethylhydrazine. Abstract : The efficient design of hypergolic-ionic-liquid (HIL) fuels with attractive features, ( e.g., short ignition delay and high specific impulse) can be achieved by fine-tuning the molecular organization comprising both cations with appropriate alkyl chains and cyanoborohydride-based hydrogen-rich anions. Attractive features of the presented derivatives were attained by combining cations with various substituents (substituted 1 H -1, 2, 4-triazol-4-ium, pyrrolidinium, ammonium and pyridinium cations) and the cyanoborohydride anion. All shown HILs display high thermal stabilities with thermal decomposition temperatures over 154 °C and possess higher densities (from 0.82 to 1.02 g cm −3 ) compared to the unsymmetrical dimethylhydrazine (UDMH, 0.793 g cm −3 ). The hypergolic ignition behavior of the propellant combination was evaluated by a drop test setup using white fuming nitric acid (WFNA) as an oxidizer and recorded using a high-speed camera. All compounds feature ignition delay times (ID) under 50 ms, while the 1-hexyl-1-methylpyrrolidin-1-ium cyanotrihydroborate congener (17 ) exhibited the shortest ID time (5 ms), which is comparable to the ID time of UDMH (4.8 ms with WFNA as an oxidizer). In addition, these HILs exhibit higher heats of formation (187.6 to 392.6 kJ mol −1 ), heats of combustion (34.39 to 47.15 kJ g −1 ) and specific impulse (176 to 205 s) compared to UDMH.